METHYLEUGENOL AND EUGENOL VARIATION IN OCIMUM BASILICUM CV. GENOVESE GIGANTE GROWN IN GREENHOUSE AND IN VITRO - M. MIELE; B. LEDDA; C. FALUGI; M. MAZZEI (Journal of Biological Research, 2024)
The Ocimum genus, collectively called basil, is an important member of the Lamiaceae family. Ocimum includes more than 100 species of herbs and shrubs from the tropical region of Asia, Africa and Central South America. Sweet basil, O. basilicum, is a common herb cultivated for culinary purposes as fresh, dried or processed. [...]